Chemical Fingerprint of Quartz Crystals Sampled Across the Lepontine Zone in the Swiss Alps - Wipperfurth, Scott A.; Johnson, Aleisha C.; Lindblad, Todd A. (My University, 2013)
Quartz crystals record the evolution of hydrothermal fluid systems that accompanied the uplift of the Swiss Alps. Crystals from twenty localities were collected along a geologic traverse across four distinct temperature regimes that define the Alpine Mountain Range. The purpose of this study was to present results on crystals extracted from the high temperature hydrothermal veins of the Lepontine Zone, representing the southern portion of the Alpine traverse.
Color poster with text, images, maps, photographs, diagrams, and graphs.
Keywords: Quartz crystals; Lepontine Zone (Alps); Posters